THE ENIAPEL BOTTOM LINE MODEL AND NATURAL TOURISM MARKETING: A MIXED METHODS STUDY OF GOSARI VILLAGE - Cempena, Ida Bagus; Ratnawati, Tri; Sitohang, Arga Christian (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: This study aims to analyze the relationship between economy, fishermen, inclusion, nature, empowerment, ecology, and local variables in the context of natural tourism development in Gosari Village, Ujungpangkah District, Gresik Regency, part of the minapolitan zone. Understanding these variables’ effects is essential for improving the sustainability and operational efficiency of Gosari Village as a tourism destination. Methods: A quantitative approach was employed through questionnaires administered to 106 respondents from various stakeholders, including Village-Owned Enterprises (BUMDes), POKDARWIS, MSMEs, and government entities. The collected data were processed using PLS 4.0. Additionally, a phenomenological study using in-depth interviews was conducted to capture the social experiences of fishing communities in Gosari Village. This dual approach provided a comprehensive understanding of the area’s tourism development dynamics. Results: The results show that fishermen significantly influence inclusion, ecology, and economy, but not empowerment. Nature is found to have a significant effect on empowerment and ecology, but not on inclusion and economy. Local variables have a significant influence on empowerment, ecology, and economy, but not on inclusion. Conclusion and suggestion: This study highlights the significant roles of fishermen, nature, and local variables in the development of natural tourism in Gosari Village, with varying impacts on inclusion, ecology, empowerment, and the economy. To enhance sustainability and operational efficiency, it is recommended to focus on digital marketing, human resource development, diversification of funding sources, the application of technology, and local empowerment policies. Additionally, the ENIAPEL Bottom Line Model is proposed as a strategy to maintain a balance between environmental, social, and economic aspects for sustainable tourism growth in the village.